Sugar-added beverages consumption among kindergarten children of Crete: effects on nutritional status and risk of obesity - Sbokos Manolis; Pateraki Maria-Styliani; Sarri Katerina; Linardakis Manolis; Kafatos Anthony (BMC, 2008)
Abstract Objective To assess the intake of sugar-added beverages such as soft drinks and commercially available fruit juices in kindergarten children, and to examine its association with obesity indices, physical activity levels and dietary habits. Methods A total of 856 children aged 4-7 years living in Crete, Greece in 2004-5 were included in this cross-sectional study. Nutrient and food intake was assessed with the use of 3-day weighed food records. Body measurements were used in order to assess BMI and waist circumference, and moderate-to-vigorous physical activity was calculated with the use of a questionnaire. Results Approximately 59.8% of all children consumed sugar-added beverages on a daily basis. High intake of sugar-added beverages (> 250 g/day) was associated with low intakes of calcium (p < 0.001), vitamin A and E (p < 0.010), fruits and vegetables (p = 0.007), and milk and yogurt (p = 0.048). Compared to non or low consumers, high consumers of sugar-added beverages (> 250 g/day) had higher BMI levels and two times greater risk of being overweight and/or obese (OR:2.35, p = 0.023). Conclusion High intake of sugar-added beverages in kindergarten children is associated with poor eating habits and inadequate nutrient intake, as well as increased risk for developing childhood obesity.